(untitled) (Texas Journal of Engineering and Technology, 2023)
This article examines the use of new methods to assess the safety of civil engineering systems. Currently, safety is very important in the design and construction of civil structures and systems and should be evaluated with appropriate methods. The new methods discussed in this article include the error and risk factor analysis method, code coverage analysis method, dangerous mode analysis method, neural network analysis method, and state space analysis method. The purpose of using these methods is to identify and find errors and risk factors in construction systems. The occurrence of failure in some civil engineering systems such as structures (such as trusses and frames), underground arterial networks (such as water and gas networks), etc., usually with a logical equation A complex or a combination of multiple failure events is expressed. Unlike the existing methods of reliability analysis, MSR and SCM methods are used in any type of system, including series, parallel and complex, and even can consider the dependence between parameters. don’t Unlike old methods, new methods do this automatically and accurately using artificial intelligence and machine learning algorithms. These methods can identify small and large errors in construction systems and increase safety and reduce the risks associated with them. The sequential combination method can be used for systems with a large number of components, without adding to the cost and time of calculations. In general, using new methods to assess the safety of civil engineering systems improves performance and reduces risks in civil systems. Considering the potential of these methods, more research is needed in the field of their use in the operational industry. Also, the results show the high speed and accuracy of this method in calculating the reliability of structural systems, compared to other existing methods